Negotiating Citizenship: Migrant Women in Canada and the Global System - Dhamoon, Rita (Labour / Le Travail, 2007)
The article reviews the book, "Negotiating Citizenship: Migrant Women in Canada and the Global System," by Daiva K. Stasiulis and Abigail B. Bakan.
Keywords: BAKAN, Abigail B.; BOOKS -- Reviews; NEGOTIATING Citizenship: Migrant Women in Canada & the Global System (Book); Nonfiction; STASIULIS, Daiva K.; WOMEN immigrants